Design and implementation of hardware in the loop simulation for electric ducted fan rocket control system using 8-bit microcontroller and real-time open source middleware - Yulnandi, Reza Aulia; Machbub, Carmadi; Prihatmanto, Ary Setijadi; Hidayat, Egi Muhammad Idris (Research Centre for Electrical Power and Mechatronics, Indonesian Istitutes of Sciences, 2017)
Hardware in the Loop Simulation (HILS) is intended to reduce time and development cost of control system design. HILS systems are mostly built by integrating both controller hardware and simulator software where the software is not an open source. Moreover, implementing HILS by using manufactured system is costly. This paper describes the design and implementation of HILS for Electric Ducted Fan (EDF) rocket by using open-source platform for development with middleware. This middleware system is used to bridge the data flow between controller hardware and simulator software. A low-cost ATMEGA 2560 8-bit microcontroller is used to calculate rocket’s attitude with Direction Cosine Matrix (DCM) algorithm and PID controller is employed to regulate rocket’s dynamics based on desired specifications. X-Plane 10 simulator software is used for generating simulated sensory data. The test results validate that HILS design meets the defined specifications, i.e. angle difference of 0.3 degrees and rise time of 0.149 seconds on pitch angle.